Nutritional Analysis and Organoleptic Test of Spinach Dimsum for Pregnant Women - Luckyto, Rezandy Alif Bima; Arief, Ria Qadariah; Lusiana, Nova (International Conference on Sustainable Health Promotion, 2025)
Pregnancy was an important phase that affected the health of both mother and fetus; therefore, fulfilling balanced nutrition needed to be considered to prevent stunting. Spinach contained iron, folic acid, and vitamin A, which played a role in preventing anemia, supporting fetal growth, and maintaining maternal health. To improve acceptability, spinach was processed into dimsum as an innovative local supplementary food that was more attractive and easier for pregnant women to consume. This study aimed to analyze the nutritional content and acceptability of spinach dimsum as a local supplementary food. Nutritional content was analyzed using the Indonesian Food Composition Table, although this calculation was limited and required further laboratory testing. An organoleptic test was conducted using a hedonic scale questionnaire involving 34 pregnant women to assess color, aroma, taste, texture, and appearance. The results showed that each (one piece serving) contained 33.08 kcal energy, 0,61 g carbohydrates, 2.90 g protein, and 2.02 g fat, along with vitamin A (35.83 µg), iron (0.24 mg), and folic acid (8.5 µg). The organoleptic test indicated that most panelists liked the color (82.4%), aroma (73.5%), taste (85.3%), texture (88.2%), and appearance (91.2%). In conclusion, spinach dimsum is suitable for use as a local supplementary food option for pregnant women to help increase their energy and folic acid intake